TAFSIR HERMENEUTIKA INTENSIONALISME DALAM PENERAPAN APLIKASI ATLAS - Sihotang, Ruth Jenny; Mulawarman, Aji Dedi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to determine the meaning of using the Audit Tools and Archives System (ATLAS) application as a financial statement auditing tool, involving Intentional hermeneutics to analyze findings based on historical context, the cultural context in the correlated and explored